THE NEED FOR IMPLEMENTATION OF LOGISTICS IN CONNECTION WITH THE REFORM OF RAILWAY TRANSPORT IN UKRAINE - Koretska, S. O. (Science and Transport Progress, 2007)
On the basis of analysis of the transporting logistic systems of foreign companies the most priorities and effective directions of the transporting logistic systems which must be developed today are represented in the article. In addition, four levels of development of the systems of logistic are described on a railway transport in Ukraine.